Students' Rights And Obligations Towards Society From The Point Of View Of Hamka - Ramadhanzi, Muhammad Kholid; Salamah, Salamah; Habibi, Surya; Fatwanti, Devi; Sofia, Veni (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This research aims to find out the rights and obligations of a Hamka. The nature of this research is that it is qualitative library research in the form of document study research. The sources used for the benefit of this research are the book Life Institutions, which is a written work by Hamka, and several books by him, which are still related to the rights and obligations of a student to society as well as several relevant literature, journals or sources needed to get students to society which are contained in the book Life Institutions by Hamka. The results obtained from this research are that a student's right to society is to have the right or freedom to live, the right to have an opinion and express it in public, the right to expand understanding of what he is interested in, the freedom to seek knowledge, the right to have his views respected, the right to be respected for himself and his property or possessions respected, the right to be criticized and accept or reject criticism from society. And the obligation of society to students is to provide freedom to live or society, obliged to respect their opinions, obliged to broaden their understanding to live in society, obliged to provide freedom to seek knowledge, respect the positions held by students, respect them and respect their property, obliged to provide criticism, where the criticism intended here is criticism that builds the quality of a work or self that is criticized, not to bring down the quality or self-confidence of the recipient of criticism. These rights and obligations need to be understood, which are useful for increasing the prosperity of social life.